Chronic recurrent multifocal osteomyelitis involving the mandible: case reports and review of the literature - Monsour, P A J (The British Institute of Radiology., 2010)
Chronic recurrent multifocal osteomyelitis (CRMO) is an aseptic inflammatory disorder of unknown cause occurring in children and adolescents. It is characterized by multifocal bone lesions with pain and swelling recurring over months to years. Lesions usually involve the metaphyses of the long bones and involvement of the jaw is rare. The clinical presentation, radiographic appearance and histology of a case of CRMO involving the mandible in an 8-year-old girl are documented. The radiographic appearance of another three cases is also described.